United States-Iran Conflict and Its Security Implications for Middle East - Otubu, Alex; Efebeh, Vincent Eseoghene; Sanubi, Franklins A. (Malikussaleh Social and Political Reviews, 2024)
This study examined at the United States -Iranian conflict and how it would affect Middle East security. This study used a historical research design, and the trend analysis technique was used to analyze the data. It was determined that the exploratory and qualitative trend analysis technique was appropriate for the type of study. This study was based on Zagare's (1996) deterrence theory, which was seen as a re-evaluation of the traditional balance of power theory. Findings showed that the core reasons for the dispute between the United States and Iran were the U.S. foreign policy, the failed extreme pressure strategy of the Biden and Trump administrations, state behaviour in the global order, innovation, domestic politics, and control and deterrence. The conflict between the United States and Iran has undermined regional security and peace. The main causes of the sanctions' futility against the Islamic Republic of Iran include Iran's economic diversification, its technological advancements, its nuclear program, its geopolitical location, people's support for the system as well as political engagement, the continued implementation of Iran's regional policies, political countermeasures, and other countries' lack of political support following Trump's decision to withdraw from the Joint Comprehensive Plan of Action. The Middle East's security was viewed as being threatened by Iran's nuclear program by the United States, Israel, and other countries in the region. The study came to the conclusion that, despite the two states' numerous problems and obstacles impeding their attempts to normalize, opportunities and hopes have always existed. The study concluded that despite their ongoing hostility and tense relationship, both nations occasionally communicate because it is in their specific national security goals. Therefore, the study suggested, among other things, that in order to prevent the United States from isolating itself from significant actors in the Middle East, the country should work to restore relations with Iran and discover productive means of resolving disagreements, starting with a return to full adherence to the JCPOA for both parties.